(untitled) (Asian-Australasian Journal of Food Safety and Security, 2018)
The samples of the cauliflowers were analyzed to assess the residue level of six insecticides (i.e.; cypermethrin, quinalphos, diazinon, malathion, fenitrothion and acephate) using GC-FTD and GC-ECD method. Out of analyzed 75 collected samples of cauliflower from farmer’s field of Jessore, Gazipur and Rangpur, 38.67% (29 from 75) were found to be contaminated with the insecticides. Many samples contained cypermethrin, acephate and fenitrothion residues. Quinalphos, acephate and fenitrothion were found as multiple product residues representing 13.79% (4 from 29) of the total contaminated samples and the rest 86.21% contained single insecticide residue. About 13.33% (10 of 75) of the total samples had residues exceeding the MRL (Maximum Residue Limit) irrespective of single or multiple insecticide residues. Malathion residue was found only in one sample from Jessore. Two samples showed diazinon residue one from Jessore and the other one from Rangpur location. The detected residue levels of both malathion and diazinon were below the MRL, which might be due to higher rate of degradation. The presence of highest residue levels of insecticides in cauliflowers may be due to its irrational and repeated use before harvest. Asian Australas. J. Food Saf. Secur. 2018, 2(1), 29-34